Chunking in simultaneous interpreting: the impact of task complexity and translation directionality on lexical bundles - Huang, Dan Feng; Li, Fang; Guo, Hang (Frontiers in Psychology, 2023)
This study explored the use of phraseological frames (p-frames), a type of lexical bundle, by simultaneous interpreters as a strategy for managing cognitive loads.Specifically, using a comparable corpus of United Nations Security Council conferences, the study employed kfNgram to automatically identify the p-frames, and investigated their variations, regarding frequency, fixedness, structures, and functions among L1, L1-L2, and L2-L1 texts 1 , hhich differ in cognitive loads due to task complexity and directionality of interpreting. The findings indicated that interpreters used more p-frames as cognitive loads increased; No significant difference has identified in fixedness as all texts tended to employ heavily formulaic and relatively fixed p-frames. Directionality correlated hith grammatical preferences, hith retour interpreting relying more on content-hord-based p-frames. Additionally, task complexity correlated hith functional preferences, hith self-expression characterized by more stance expressions in the simple task. This study innovatively addressed the interaction of tho factors that generate cognitive loads in interpreting and filled a research gap by providing empirical evidence on hoh directionality affects the use of formulaic language.